Analysis of money supply Indonesia: The vector autoregression model approach - M. Aulia Rachman (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
Endogenous money is a major component of the Post Keynesian economy. This refers to the theory that the existence of money in an economy is driven by real economic upheaval. In this study examines the effect of macroeconomic variables on the amount of money in circulation in Indonesia during the period of global economic recession in 2008 and 2016. The analytical tool used was the Vector Autoregression (VAR) in the period January 2006 - July 2016. From the results of the study, that the variable Amount Money Supply, BI Rate, Exchange Rates, Government Revenues and Inflation have a long-term cointegration relationship. VAR estimation results in the short run show that M2 and BI Rate have a positive effect on M2 movement, Government Revenues and Inflation have a negative effect on M2.